Seismic anisotropy in southern Costa Rica confirms upper mantle flow from the Pacific to the Caribbean - Levin, Vadim (2020)
Surrounded by subducting slabs and continental keels, the upper mantle of the Pacific is largely prevented from mixing with surrounding areas. One possible outlet is beneath the southern part of the Central American isthmus, where regional observations of seismic anisotropy, temporal changes in isotopic composition of volcanic eruptions, and considerations of dynamic topography all suggest upper mantle flow from the Pacific to the Caribbean. We derive new constraints on the nature of seismic anisotropy in the upper mantle of southern Costa Rica from observations of birefringence in teleseismic shear waves. Fast and slow components separate by ~1 s, with faster waves polarized along the 40°–50° (northeast) direction, near-orthogonally to the Central American convergent margin. Our results are consistent with upper mantle flow from the Pacific to the Caribbean and require an opening in the lithosphere subducting under the region.